Recent Developments in the Nigerian Company Law - Babalola, Afe; Chigbo, Clement C. (ABUAD Private and Business Law Journal, 2018)
One of the various modes of doing business is to form a registered company. Prospective business persons and entrepreneurs who are desirous of pursuing commercial ventures in Nigeria would be forming companies limited by shares (that is a company where the liability of the shareholders for the debts of the company is limited to the amount unpaid on their shares). There are other types of company and business entities that can be registered in Nigeria (e.g. the company limited by guarantee and trust companies etc.). The contribution of the Company Law of Nigeria to orderly regulate business and economic affairs need not be overemphasized. The earliest known piece of company legislation of significance in Nigeria was the Company Act of 1912 which at first applied only to the colony of Lagos. It was later extended to the whole of the country. Plainly, students and practitioners will wish to know something of the ways in which the company law of tomorrow is likely to develop if the reforms which are now being planned or proposed receive the blessing of the present government. Thus it has been necessary to discuss some of the innovative changes being proposed in the anticipated Amendment to our Company Legislation. It became apparent that the entire Nigerian corporate landscape was heavily hamstrung by several provisions in the CAMA 2004 which have been described as impeding modern business practices in the light of national and global reforms. It has therefore been determined that the provisions of the current Act are not in tandem with global trends and that same requires extensive amendments to make the Act more contemporary and relevant. This commentary discusses/examines some of these amendments in context.